Evaluation of The Quality of Pharmaceutical Care and Identification of Human Resources and Infrastructure in The Pharmacy Installation of Hospital in Sukoharjo in 2023 - Pinasthika, Shinta; Nugraheni, Ambar Yunita (Pharmacon: Jurnal Farmasi Indonesia, 2024)
The fulfillment of pharmaceutical Minimum Service Standards (MSS) an important role in improving the quality of pharmaceutical services and public health. This study aims to evaluate the quality of pharmaceutical care following the pharmaceutical minimum service standards as well as the identification of human resources (HR) and infrastructure facilities at the Hospital Pharmacy Installation in Sukoharjo. This type of research is descriptive non-experimental. Samples in the study included prescriptions and patients. Samples in the study included prescriptions and patients. MSS data on indicators of dispensing time for drug services, indicators of prescription suitability with the formulary and patient satisfaction analyzed based on Menkes RI Number 30 of 2022. Data on HR and infrastructure were analyzed based on Menkes RI Number 56 of 2014 and Menkes RI Number 72 of 2016. The results showed the indicator dispensing time does not meet the standard because dispensing time ≤ 60 minutes is 45.66% (less than standard of 80%). The results on the indicator of the suitability of prescriptions with the formulary are 89.5% (≥80%), and the patient satisfaction indicator is 91.25% (76.61%) so it has met the standard. The results of HR identification based on the classification of the number of pharmaceutical personnel have met the standard. However, classification based on pharmacist workload and identification of facilities and infrastructure does not meet the standard.